Evaluation of the preparedness of graduating pharmacy students in the implementation of a smoking cessation program in the Philippines - Florentino, Donnerie V.; Liban, Lara Alyssa B.; Pangilinan, Ysabelle T.​ (2017)
Smoking cessation programs have been initiated and implemented by pharmacists in different countries around the world. Considering the developing role of pharmacists in the Philippines, pharmacy students must be well equipped with the necessary knowledge to effectively facilitate a smoking cessation program in order to fulfill this expanding role. This study aimed to evaluate the preparedness of graduating pharmacy students in the implementation of a smoking cessation program, by assessing their knowledge on smoking and cessation, and their attitudes on smoking, cessation, and smoking cessation programs. The research used a descriptive, cross-sectional design which utilized a questionnaire. Mean total scores, independent t-tests, Chi-square, and one-way ANOVA were performed to analyze the data. Responses from 197 graduating pharmacy students from PACOP- member schools in Metro Manila were obtained corresponding to an 80.41% response rate. Of the 197 participants, only 1.52% passed the criteria set for knowledge based on the passing criteria set for pharmacist licensure examinations. The topic on tobacco products and harmful effects of smoking had the highest passing rate, while the topic on pharmacologic and non-pharmacologic interventions for smoking cessation had the lowest passing rate. Factors which have a statistically significant effect (p < 0.05) on knowledge score are year level (p = 0.0124), age (p = 0.0000), patient interaction (p = 0.0128), specifically experiences on counselling and medication history taking. For attitudes, 76% of the participants have a positive attitude towards smoking, 94% have a positive attitude towards smoking cessation, and 93% towards the implementation of a smoking cessation program. The results provide a valid indication that the students are not prepared to facilitate a smoking cessation program in terms of the necessary knowledge needed, but are prepared in terms of their attitudes. Integration of smoking and cessation, focusing on knowledge in the areas of epidemiology and pharmacologic and non-pharmacologic interventions, in the academic curriculum and smoking cessation training program is recommended.